2017
DOI: 10.21909/sp.2017.02.734
|View full text |Cite
|
Sign up to set email alerts
|

We expect stocks to rise, but we do not know when and which ones: Excessive optimism in predicting future stock indices returns

Abstract: In this study, we analyze whether: 1) financial professionals manifest lower excessive optimism in predicting future stock indices returns; 2) excessive optimism occurs more when predicting future returns of indices reporting profits than indices reporting losses 3) more long-term predictions are more optimistic than short-term predictions. Three groups of participants (n = 251) -investment managers, financial advisors, and lay men predicted future returns of six stock indices in three forecasting horizons by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
1
2
0
Order By: Relevance
“…Influence of expertise on personal and social forms of optimism bias (Aim 3). In the personal domain, optimism bias has been found to be reduced (but not totally eliminated) for increasing levels of experience with a to-be-evaluated scenario (e.g., Grezo, 2017;Helweg-Larsen and Shepperd, 2001;Weinstein, 1980). Here, we show that this effect can also be seen in the social domain.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…Influence of expertise on personal and social forms of optimism bias (Aim 3). In the personal domain, optimism bias has been found to be reduced (but not totally eliminated) for increasing levels of experience with a to-be-evaluated scenario (e.g., Grezo, 2017;Helweg-Larsen and Shepperd, 2001;Weinstein, 1980). Here, we show that this effect can also be seen in the social domain.…”
Section: Discussionsupporting
confidence: 49%
“…Third, research on optimism bias has shown an influence of prior experience with a situation (e.g., Grezo, 2017;Helweg-Larsen and Shepperd, 2001;Weinstein, 1980). Generally, it has been observed that personal optimism bias decreases as experience with (or knowledge about) an event increases (Barnoy et al, 2003;Campbell et al, 2007;Cho et al, 2010).…”
mentioning
confidence: 99%
“…Especially financial advisors, who rate themselves as better than others, often show very poor performance (even compared to lay people) in financial analyzing or predicting future prices (e.g. Staël von Holstein, 1972; Glaser et al , 2013; Menkhoff et al , 2013; Grežo, 2017). In such a case, using financial advices and services of overconfident individuals could potentially lead to suboptimal decisions and financial losses.…”
Section: Discussionmentioning
confidence: 99%